2011
DOI: 10.1017/s0022029911000811
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative staphylococci from non-mastitic bovine mammary gland: characterization ofStaphylococcus chromogenesandStaphylococcus haemolyticusby antibiotic susceptibility testing and pulsed-field gel electrophoresis

Abstract: During routine microbiological examination of milk samples from dairy cows without clinical signs of mastitis, quarter milk samples of 231 dairy cows from 12 herds were investigated for the presence of coagulase-negative staphylococci (CNS). The isolates were identified on the basis of colony morphology, Gram staining, catalase and coagulase test and the commercial kit, API Staph. CNS was detected in 29% (67/231) of the cows. A total of seven CNS species were identified with the most prevalent being Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Consequently, contagious transmission among cows seems to be an important route for new IMI caused by S. chromogenes. Another possible reason for the high prevalence of S. chromogenes is its resistance to antibiotics (44) and its ability to persist in the mammary gland. Taponen et al (45) reported that 54.5% of IMI caused by S. chromogenes persisted throughout lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, contagious transmission among cows seems to be an important route for new IMI caused by S. chromogenes. Another possible reason for the high prevalence of S. chromogenes is its resistance to antibiotics (44) and its ability to persist in the mammary gland. Taponen et al (45) reported that 54.5% of IMI caused by S. chromogenes persisted throughout lactation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either the host immune response or differences in NAS must be taken into account when discussing bacterial virulence and commensalism. Interestingly, S. chromogenes is most frequently isolated from milk and skin (69), but not from other environmental sources, suggesting that it is likely host-adapted (49,62,(70)(71)(72). Literature suggests that this species is largely isolated from samples of bovine origin, although it can be isolated from the milk of other dairy ruminants including goats and dairy buffalo (73).…”
Section: Staphylococcus Chromogenes: the Dominant Nas Speciesmentioning
confidence: 99%
“…In PFGE, the total genomic DNA is restricted by endonuclease that cleaves infrequently, and the fragments are analyzed by gel-electrophoresis with alternating power and direction of the electric current. Analysis using PFGE enables simple, accurate and reproducible comparison of isolates for genetic relatedness (Tenover et al, 1995) and several literature reports have documented the use of PFGE in typing staphylococcal species from bovine udder (Mørk et al, 2012; Pate et al, 2012; Bexiga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%